AUDIT E-LEARNING DENGAN FRAMEWORK COBIT 5.0 DI MASA PANDEMI COVID-19 - Rini Nurlistiani; Neni Purwati; Supri Yanto (IIB Darmajaya, 2021)
The first Coronavirus Disease-2019 (COVID-19) outbreak appeared in Wuhan, China on December 01, 2019 and was declared a pandemic by WHO (world health organization) on March 11, 2020[1]. This condition requires all levels of society to stay at home (WFH), worship, work and study all at home. So that educational institutions are also required to follow government regulations and innovate learning processes that must continue when natural disasters or global pandemics occur through online learning with the aim of improving the quality of learning. Darmajaya Institute of Informatics and Business uses information technology in the form of online learning media called E-Learning for students and lecturers. This of course makes students and lecturers have to adapt in using the information technology. This E-Learning technology is used intensely by students and lecturers (both permanent and external lecturers) of IIB Darmajaya, so that in conditions in the field there are many shortcomings in the E-Learning service at IIB Darmajaya. One way to measure the governance and capability level of E-Learning services at IIB Darmajaya is to conduct a governance audit on the E-Learning services. In this study, a governance framework is needed in the form of Control Objective for Information and Related Technology 5 (COBIT 5.0) which can provide benefits for an agency in achieving strategic goals and optimizing services from information technology.Keywords—Audit Tata Kelola, E-Learning, COBIT 5.0, Maturity Level, Capability Level.